2014
DOI: 10.1074/jbc.m113.524801
|View full text |Cite
|
Sign up to set email alerts
|

Physical Interaction between Bacterial Heat Shock Protein (Hsp) 90 and Hsp70 Chaperones Mediates Their Cooperative Action to Refold Denatured Proteins

Abstract: Background: HtpG, a bacterial heat shock protein 90 (Hsp90), is essential for thermotolerance in some prokaryotes. Results: HtpG functions with DnaK2/DnaJ2/GrpE to assist unfolding/folding of denatured proteins in both ATP-dependent and -independent fashions. Conclusion: The cooperative action of HtpG and DnaK2 might play a key role under stress. Significance: This might be the first sign of a prokaryotic Hsp90 foldosome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 37 publications
(53 reference statements)
6
53
0
Order By: Relevance
“…In addition to ATP, TRAP1-dependent protein folding also requires the functional cooperation of the mitochondrial Hsp70 system. The latter supports a direct physical interaction, as was recently reported for cytosolic Hsp90 chaperones (5)(6)(7)50), and opens up new avenues for drug development by targeting the specific interaction between mitochondrial chaperones.…”
Section: Discussionmentioning
confidence: 81%
“…In addition to ATP, TRAP1-dependent protein folding also requires the functional cooperation of the mitochondrial Hsp70 system. The latter supports a direct physical interaction, as was recently reported for cytosolic Hsp90 chaperones (5)(6)(7)50), and opens up new avenues for drug development by targeting the specific interaction between mitochondrial chaperones.…”
Section: Discussionmentioning
confidence: 81%
“…This observation led to the proposal that Hsp90C participates with other stromal chaperones as part of the import motor. This hypothesis is supported by studies in cyanobacteria, Chlamydomonas and Arabidopsis demonstrating that the bacterial/organelle Hsp70 and Hsp90 family members interact in complexes containing additional co-chaperones [171-173]. …”
Section: Nature and Function Of Tic Complexesmentioning
confidence: 93%
“…Hitoshi Nakamoto (Saitama University, Saitama, Japan) showed that a cyanobacterial mutant of HtpG is impaired under heat stress. HtpG and DnaK were found to directly interact (whereas in eukaryotes this is mediated by HOP), and HtpG to collaborate with DnaK to assist in refolding of denatured proteins in either an ATP-dependent or an ATPindependent fashion 15 . Contrary to expectations, DnaK-HtpG collaboration in an m e e t i n g r e p o r t npg the mechanisms by which Hsp90 recognizes non-native states of client proteins can be explored.…”
Section: Hsp90 Orthologs: Grp94 and Htpgmentioning
confidence: 99%